The World Book Encyclopedia of Science: Volume 5: The Planet World - Ruth Binney; Robin Kerrod (Chicago World Book, Inc., 1995)
World Book, Inc. a Scott Fetzer Company Chicago London Sydney Toronto . Verlagsgruppe Bertelsmann International, Munich
v. 1. The heavens -- v. 2. Physics today -- v. 3. Chemistry today -- v. 4. The planet Earth -- v. 5. The plant world -- v. 6. The animal world -- v. 7. The human body -- v. 8. Men and women of science ; index.
Includes indexes. 8 volumes : illustrations (some color)
Keywords: Encyclopedias (3GdehShYGJs; Science -- Dictionaries; General